Topical Application of Metal Allergens Induces Changes to Lipid Composition of Human Skin - Knox, Sophie; Hagvall, Lina; Malmberg, Per; O'Boyle, Niamh M. (Frontiers in Toxicology, 2022)
Lipids are an important constituent of skin and are known to be modified in many skin diseases including psoriasis and atopic dermatitis. The direct effects of common metallic contact allergens on the lipid composition of skin has never been investigated, to the best of our knowledge. We describe skin lipid profiles in the stratum corneum and viable epidermis of ex vivo human skin from a female donor upon exposure to three metal allergens (nickel, cobalt and chromium) visualised using time-of-flight secondary ion mass spectrometry (ToF-SIMS), which allows for simultaneous visualisation of both the allergen and skin components such as lipids. Multivariate analysis using partial least squares discriminant analysis (PLS-DA) indicated that the lipid profile of metal-treated skin was different to non-treated skin. Analysis of individual ions led to the discovery that cobalt and chromium induced increases in the content of diacylglycerols (DAG) in stratum corneum. Cobalt also induced increases in cholesterol in both the stratum corneum and viable epidermis, as well as monoacylglycerols (MAG) in the viable epidermis. Chromium caused an increase in DAG in viable epidermis in addition to the stratum corneum. In contrast, nickel decreased MAG and DAG levels in viable epidermis. Our results indicate that skin lipid content is likely to be altered upon topical exposure to metals. This discovery has potential implications for the molecular mechanisms by which contact allergens cause skin sensitization.